TEACHER QUESTIONS IN JUNIOR HIGH SCHOOL CLASSROOM - Delvidus Nong Bapan (Widya Mandala Surabaya Catholic University, 2016)
This study described the types of questions, examined the frequency of the questions types, found out the reasons teacher addresses the high frequency questions as well as what the learners responded to those questions in seventh graders of Cita Hati Junior High School. The results demonstrated that both display and referential questions were asked by the teacher in his teaching. The teacher’s reasons of asking referential questions were to dig more information and build interaction with the students. Both referential and display questions could produce students’ long verbal form responses. Furthermore, the students could also produce not only longer but also more complex responses toward referential questions. By asking referential questions, his teaching was more alive since his students were in high English proficiency. Above all, it shows that the teacher question types were not only used to acquire the form of students’ responses but also to achieve the teacher’s purposes of asking questions.